Pré-teste de protocolo de entrevista motivacional para prevenção da cárie dentária na primeira infância - Fabyane Cota Ribeiro Duarte (2024)
Early childhood caries represent a chronic and relevant problem for public health. Since it is a preventable medical condition, promoting prevention is necessary. Nevertheless, the traditional prevention in Dentistry has not shown favorable outcomes due to its imposing and prescriptive approach. The multifactorial view of diseases, considering the social, economic and cultural determinants involved in this process, has demanded new preventive approaches in the health context, also including early childhood caries.Thus, a communication strategy aimed at parents, who are the child’s reference point in their formative process, has been shown to be effective in several studies. This approach, originated in psychotherapy, is known as Motivational Interviewing (MI). In Brazilian Dentistry, the subject is still little exploresand MI is little apllied by oral health teams. The explanation may be the lack of a guiding roadmap and the lack of training of the teams. Therefore, the aim of this study was to pre-test the protocol proposed by Weinstein, Harrison and Benton and to offer an introductory course on MI theory. Based on the MI protocol aimed at addressing factors related to dental caries in early childhood, which was translated and validates in Brazil in 2020, a pre-tes was carried out on a sample of 23 participants with caracteristics of the protocol's target population, to check their understanding of the questions .The researcher previously underwent Training that enable her to acquire skills to employ the principles of MI before entering the field. The methodological study was carried out with parents/guardians of children medically assisted by the Dentistry School of the Federal University of Minas Gerais and the Primary Healthcare in Betim/MG, being mothers between 20 and 30 years old, with high school education and income between 501 and 3,000. The interview audios were recorded and transcribed to ensure that the approach of the interviewer followed the principles of MI. A field notebook was also used to record important aspects of data collection.The protocol underwent structural adaptations in the pretest which enabled fluidity and coherence for its use in public service, was largely well understood by all socioeconomic profiles interviewed, displayed only two questions with a greater number of participants who did not understand (n=7). The study resulted in the Weinstein Protocol, tested on Brazilian individuals, to be made available to oral health teams as a guiding instrument that enables training in the MI approach to prevent early childhood caries. As a techical product of this study, an a introductory course on MI in oralhealth was offered. The course's target audience was oral health profissionals from the municipality of Betim (dental surgeons, oral health assistants and technicians), FAO-UFMG ubdergraduate students and the other external sakholders. The course lasted 8 hours, divided into two days. There were 47 registrations, with 16 and 20 participants actually taking part on the first and second day, respectively. The participant' s overall assessment of the course was good (29,4%) and excellent (70,6%)